Prayer in Islamic Thought and Practice - Yasmin Amin (International Institute of Islamic Thought, 2015)
Prayer in Islamic Thought and Practice, part of the “Themes in Islamic History” series, is divided into an introduction, five chapters, and a short conclusion. In the introduction, the author focuses on ṣalāt, the five canonical daily prayers. The book offers a historical study based mainly on pre-modern Arabic sources from the ninth to the sixteenth century, which is supplemented by secondary and modern non-Arabic sources to cover major changes in the practice or interpretation of ṣalāt (p. 2). Katz quotes the views of pre-modern and modern western observers, thereby showing their sympathy and admiration for the concentration, devotion, seriousness, reverence, regularity, egalitarianism, and inclusiveness associated with it. In Chapter 1, “Canonical Prayer and Supplication, Development, and Rules,” Katz traces the etymology of the term’s linguistic origin, historic significance, and pre-Islamic meaning. She quotes Q. 31:17 to show that it was not used exclusively in reference to monotheism or the Abrahamic faiths. Șalāt is explained both in terms of the prayer’s religious content and physical postures. Its validity is discussed and shown to be dependent upon several conditions, such as the knowledge of specific times, ritual purity, orientation to Makkah, and intention. The prayer components (arkān) are also dealt with in detail ...